Ineffective health management in hemodialysis patients: content analysis - Maria das Graças Mariano Nunes de Paiva; Jéssica Dantas de Sá Tinôco; Fernanda Beatriz Batista Lima e Silva; Juliane Rangel Dantas; Marcos Venícios de Oliveira Lopes; Ana Luisa Brandão de Carvalho Lira
ABSTRACT Objective: To analyze the content of the nursing diagnosis Ineffective Health Management in hemodialysis patients. Method: The Nursing Diagnoses Validation Model by Lopes, Silva and Auraújo was used in this research. A semi-structured questionnaire and evaluated the definition, location, defining characteristics, and related factors of the diagnosis Ineffective Health Management was answered by 22 experts in nursing diagnosis. The analysis was conducted from August 2014 to January 2015. Results: Experts considered the proposed definition and the current location in the taxonomy II by the NANDA-I, Domain 1 Health Promotion, Class 2 Health Control, adequate to the diagnosis. The adequacy level adopted at 85% or p > 0.05 were above 10 defining characteristics and 24 related factors. Experts also suggested that one defining characteristic should become a related factor and that three factors should turn into defining characteristics. Conclusion: A new proposal was developed for the diagnosis under study after the analysis of experts.